Keabsahan Pemilihan Ulang Dalam Pemilihan Kepala Desa Serentak - Meute, Anjelin Melna Adriana; Pietersz, Jemmy Jefry; Irham, Muhammad (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: There is no regulation explaining the re-election of village heads.Purposes of the Research: The purpose of this study is to find out and analyze the arrangements for re-election of simultaneous village head elections, to find out and analyze the legitimacy of re-election arrangements for simultaneous village head electionsMethods of the Research: This research used normative research method.Results of the Research: The results of the study, it was found that re-election was not regulated in Indonesian legislation even though there were settlement disputes which culminated in the process of resolving village head elections to legal remedies and the validity of re-election was invalid, if fraud and injustice were found in village head elections and carried out based on the applicable statutory provisions, so that there must be arrangements regarding re-election.